Strategi Pemasaran UMKM Donat Seribuan di Jl. Pancing dalam Meningkatkan Daya Saing Produk Lokal - Annisa Febrianda; Siti Nurhaliza; Rania Atika Putri; Zainarti Zainarti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the marketing strategies implemented by the Donat Seribuan MSME located on Jl. Pancing in enhancing the competitiveness of local products amid increasingly intense market competition. As a pillar of the people's economy, micro, small, and medium enterprises (MSMEs) play a vital role in supporting national economic growth but often face challenges related to market access and the development of effective promotional strategies. This research adopts a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and documentation. The findings indicate that Donat Seribuan applies a hybrid marketing strategy, combining traditional promotion methods (word-of-mouth, affordable pricing, strategic location) with the use of social media to reach a broader consumer base. The implementation of community-based marketing, product storytelling, and collaboration with local micro-influencers has proven effective in strengthening product image and building customer loyalty. These results highlight the importance of innovative, locally tailored marketing strategies to sustainably enhance MSME competitiveness.